Millions on the move: Bridging research and policy to address growing global challenges of displacement and migration - Kosec, Katrina; Carrillo, Lucia (International Food Policy Research Institute, 2025)
Globally, one in every seven people is now a migrant or a refugee. Displacement has reached record highs, reshaping communities worldwide. As of 2024, close to 120 million people had been forcibly displaced and more than 300 million were living outside their country of birth. By 2050, projections indicate that over 200 million people will be displaced in their own countries as a result of climate change alone.